2022
DOI: 10.1002/aff2.75
|View full text |Cite
|
Sign up to set email alerts
|

Economic feasibility of fish cage culture in Lake Victoria, Kenya

Abstract: Fish cage culture has rapidly grown throughout Lake Victoria's shores, with Nile tilapia (Oreochromis niloticus) being the primarily cultured species. However, there is inadequate information on its economic viability. The study investigated the economic feasibility of fish cage farming system in Lake Victoria, Kenya, by evaluating the relationship between cost of inputs and revenue from fish sales and analysing the overall profitability of the fish cage culture in the lake. Systematic sampling was employed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…It was found that feed expenses form the highest cost component of ₹ 302170 (86.27%) among variable costs. Gawa et al (2021) and Obiero et al (2022) also found the feed cost as the single most important cost component in inland water cages of Jharkhand, India and Kenya respectively. In case of annual fixed cost, permanent human labour formed the highest cost component of ₹ 2 lakhs (51.53%), followed by depreciation ₹ 112560 (29%) and interest on fixed capital ₹ 75600 (19.48%).…”
Section: Resultsmentioning
confidence: 95%
“…It was found that feed expenses form the highest cost component of ₹ 302170 (86.27%) among variable costs. Gawa et al (2021) and Obiero et al (2022) also found the feed cost as the single most important cost component in inland water cages of Jharkhand, India and Kenya respectively. In case of annual fixed cost, permanent human labour formed the highest cost component of ₹ 2 lakhs (51.53%), followed by depreciation ₹ 112560 (29%) and interest on fixed capital ₹ 75600 (19.48%).…”
Section: Resultsmentioning
confidence: 95%
“…One of the most significant barriers to the expansion of the aquaculture business is the high cost of feeds (Iliya et al., 2023; Obiero, Brian Mboya, et al., 2022). Small‐scale farmers in SSA employ low‐input, low‐output aquaculture to maintain production, relying mostly on naturally occurring ecosystem services and feed (Williams & Rota, 2011).…”
Section: Resultsmentioning
confidence: 99%